Saicho: The Establishment of the Tendai School. Paul Groner. - Barrett, T. H. (Buddhist Studies Review, 2002)
Saicho: The Establishment of the Tendai School. Paul Groner. University of Hawai'i Press, Honolulu 2000. 337 pp. Pbk $35.00. ISBN 0-8248-2371-0.